Impact of Vitamin D on the Occurrence and Development of Intestinal Diseases: A Systematic Review and Meta-analysis of Randomized Controlled Trials - Liu, Jiewei; Wang, Yue; Zou, Yanhong; Li, Chunyu (Combinatorial Chemistry & High Throughput Screening, 2023)
Aim: To determine the impact of vitamin D on the occurrence and progression of intestinal disorders, the authors of this study have conducted a systematic review and meta-analysis. Background: Vitamin D regulates inflammation and immunity in association with reducing the disease symptoms of several gastrointestinal diseases, including inflammatory bowel diseases (IBD), Crohn’s disease (CD), ulcerative colitis (UC), and colorectal cancer (CRC). However, the exact role of vitamin D in the occurrence and development of intestinal diseases is unclear so far. Methodology: The relevant studies were searched in PubMed and screened based on inclusion and exclusion criteria. The quality of full-text studies was assessed using National Heart, Lung, and Blood Institute (NIH) scale. The study was conducted as per the PRISMA guidelines. The overall estimate was calculated in terms of risk ratio with a 95% confidence interval. The publication bias was assessed qualitatively using a funnel plot, and heterogeneity among studies was calculated using I2 statistics. All analyses were done using RevMan 5.0. Results: The overall risk ratio using random effect model was found to be 0.89 (0.70, 1.12), which indicates the non-significant role of vitamin D in the occurrence and development of intestinal diseases as compared to the non-vitamin D group. However, after exclusion of studies with low and high sample sizes, a significant reduction in intestinal diseases was observed in the vitamin D group as compared to the non-vitamin D group. Further, no heterogeneity among the studies was observed. Conclusion: Based on available evidence, vitamin D might play a significant role in the reduction of intestinal diseases; however, more studies with high sample sizes are required to draw a valid conclusion.
Keywords: systematic review